Multi-layered electroless Ni–P coatings on powder-sintered Nd–Fe–B permanent magnet - Chen, Zhong (2012)
This paper has shown a successful protective coating scheme for powder-sintered Nd–Fe–B permanent magnet using multi-layered electroless nickel (EN) deposition. A low-phosphorus nickel layer is plated with an alkaline EN solution first, followed by a high-phosphorus nickel layer plated with an acidic solution. An additional topcoat by medium-phosphorus nickel on the high-phosphorus coating is also explored. It is shown that the high-phosphorus nickel layer coated in acidic solution provides the best corrosion protection because of its dense amorphous structure. The medium phosphorus topcoat is also dense and is able to provide reasonable corrosion resistance. The low-phosphorus layer itself does not have enough corrosion resistance; its main role is to provide an intermediate coating on the powder-sintered magnet. X-ray diffraction measurement shows that the low-phosphorus coating consists of nano-crystallines, and the high- and the medium-phosphorus coatings are dominated by amorphous structure. Microscopic observation and scratch test on these composite coatings demonstrate good adhesion between the magnet and the coatings. Remanence and coercivity of the plated magnet decrease with the applied coatings, but measured values are still very attractive for practical applications among known hard magnets.